Deflux® Endoscopic Treatment of Vesicoureteral Reflux (VUR) in Japan - Murakami, Hiroshi (Frontiers in Pediatrics, 2022)
Introduction: To present the results of a multi-institutional outcome analysis conducted to determine the extent of endoscopic Deflux® injection for treating primary vesicoureteral reflux in Japan. Methods: A 22-question survey was distributed to 174 certified pediatric urologists (Ninteii in Japanese) and councilors of the Japanese Society of Pediatric Urology working at 140 centers to determine the usage and clinical efficacy of Deflux® for treating primary vesicoureteral reflux in Japan. Results: 43/140 (30.7%) centers participated, which exceeded participation rates of 27.9% and 18.0% for similar surveys conducted in America in 2006 and 2014, respectively. Deflux® was administered at 43 centers using subureteral transurethral injection (n=19; 44.2%), hydrodistention implantation (n=5; 11.6%), or Double hydrodistention implantation (n=19; 44.2%) and was the first-line treatment for primary vesicoureteral reflux at 39 (90.7%) centers. Overall, 1563 ureters were treated in 1076 patients. The male:female ratio was 527:549; mean follow-up was 5.1 years (range: 3.2 years-8 years); mean age at diagnosis of primary vesicoureteral reflux was 4.2 years, and mean age at 1st Deflux® treatment was 6.2 years. Overall cure rates were 65.3% after one Deflux® treatment, 75.3% after two, and 77.3% after three. Conclusion: To the best of our knowledge, this is the first multi-institutional outcome analysis of Deflux® usage for primary vesicoureteral reflux in Japan.